2015
DOI: 10.1007/s00240-015-0788-y
|View full text |Cite
|
Sign up to set email alerts
|

Management of stone disease in infants

Abstract: Evaluating and treating renal stone disease in infants are technically challenging. In this study, we evaluated the surgical treatment of renal stones in children under 1 year of age. We retrospectively reviewed the records of patients under 1 year old who were treated with ESWL, endourological or open surgical procedures for renal stone disease between January, 2009 and December, 2012. The patients' age, gender, stone size, stone location and number, complications, stone-free status, and postoperative complic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 32 publications
(34 reference statements)
0
7
0
2
Order By: Relevance
“…Besides, medical expulsive therapy such as alphablocker (tamsulosin, terazosin) or calcium channel blockers (nifedipine) may facilitate the passage of small stones by relaxing ureteral smooth muscle. Actually, tamsulosin is wildly prescribed for pediatric nephrolithiasis (59)(60)(61)(62). The stone passage may take more than one month and in this period, the patients need appropriate care and followup.…”
Section: Acute Managementmentioning
confidence: 99%
“…Besides, medical expulsive therapy such as alphablocker (tamsulosin, terazosin) or calcium channel blockers (nifedipine) may facilitate the passage of small stones by relaxing ureteral smooth muscle. Actually, tamsulosin is wildly prescribed for pediatric nephrolithiasis (59)(60)(61)(62). The stone passage may take more than one month and in this period, the patients need appropriate care and followup.…”
Section: Acute Managementmentioning
confidence: 99%
“…Açık operasyona dönülen hastaların 5 yaş altında ve sistin taşlı olgular olduğu görül-mektedir (12) . Klinik deneyimimizin geliştiği sonraki yıllarda üreter taşlarında açık operasyona dönüşümüz olmadığı gibi, URS ve RIRS girişimlerini bir yaş altındaki hastalarımızda bile başarı ile uygulanabildiği-ni görmekteyiz (10,11) . Çocuklardaki RIRS uygulamalarında yineleyen girişimlerin taşsızlığı sağlamak için gerekeceği akılda tutulmalıdır.…”
Section: Sonuçlarunclassified
“…Vü-cut dışı şok dalgaları ile üriner sistem taşlarının kırı-labilmesi tedavide devrim yaratmışsa da bazı taşların şok dalgaları ile kırılamaması, çocuklarda işlemin uygulanması için genel anestezi gerekmesi, 15 mm'den büyük taşlarda ve özellikle böbrek alt pol taşlarında başarının düşük olması farklı tedavi girişimlerinin gündeme gelmesine neden olmuştur (5)(6)(7)(8) . Özellikle son 20 yılda gelişen endoskop ve görüntüleme sistemleri sayesinde erişkinlerde rutin hâle gelen bazı uygulamalar çocuklarda da yaygın olarak kullanılma-ya başlanmıştır (9)(10)(11)(12) . Üreteroskopi (URS) ve perkutan nefrolitotomi (PNL) uygulamaları günümüzde çocuk üriner sistem taşlarının tedavi seçenekleri içerisinde kılavuzlara girerek rutin uygulamada yer almaktadır (13) .…”
unclassified
“…It has been reported that PCNL is more efficacious and less invasive, and is associated with less blood loss than open surgery, which was said to be performed more often in pediatric patients. [ 4 , 5 ] For larger kidney stones (greater than 20 mm), PCNL has been recommended as the first-line treatment in adults. [ 6 ] At the same time, the development of smaller endoscopes for stone disintegration has resulted in ureteroscopy being more frequently used to treat kidney stones in children.…”
Section: Introductionmentioning
confidence: 99%